Dlaczego Wenus sprzyjała Portugalczykom? O roli rzymskiego antyku w traktacie Kwiaty Hiszpanii, wspaniałości Portugalii (1631) Antónia de Sousa de Macedo - Działak-Szubińska, Anna (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
The article brings forth an analysis of the antiquity- evoking themes displayed by the seventeenth-century treatise Flores de España, excelencias de Portugal (1631) by António de Sousa de Macedo (1608–1682). The author tellingly acknowledges the Roman heritage of the Iberian Peninsula, a fact that becomes intimately entwined with the patriotic narration of the origins of the nation. Antiquity is seen as the source of national pride and a handy weapon to protect anything Portuguese when the Iberian Union (1581–1640), which brought together Portugal and Spain, was in decline.